Part and tool flow management in multi-cell flexible manufacturing system - (:unkn) unknown (IEEE, 1997)
Simulation techniques have been proven as reliable and powerful tools in the design, development, evaluation and operation of manufacturing systems. The following paper presents a simulation-based work done for the part and tool now management modeling in a multi-cell flexible manufacturing system (FMS). The objective of this research was to develop a simulation model which could analyze the system in detail, and provide a basis for analyzing the effects of part and tooling strategies on major cell performance measures. An overview of the system is given and an example application is presented to illustrate how the part and tool now management simulation design system operates.